Experimental study on the fracture toughness of rust stone under mixed mode loading condition. (November 2015) - Hua, W.; Dong, S.; Xu, J.
Abstract : An experimental study on the fracture toughness of rust stone under mixed mode loading conditions has been carried out with 18 central straight through Brazilian disc specimens. The test results and theoretical values based on the generalised maximum tangential stress criterion are also discussed in this paper. The results show that the pure mode I and pure mode II fracture toughness are 1·01 and 1·51 MPam 0·5, respectively. The pure mode II fracture toughness is 1·49 times of the pure mode I fracture toughness, which is larger than the value of 0·87 obtained by the maximum tangential stress criterion. The T -stress and the size of fracture process zone ( r c ) have a great influence on the crack propagation path and mixed mode fracture toughness of rock materials. The generalised maximum tangential stress criterion, which takes into account the T -stress, can predict the experimental results very well.